2011
DOI: 10.1142/s0219720011005604
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Valid Topologies of the Secondary Structure Elements Using a Constraint Graph

Abstract: Electron cryo-microscopy is a fast advancing biophysical technique to derive three-dimensional structures of large protein complexes. Using this technique, many density maps have been generated at intermediate resolution such as 6-10 Å resolution. Although it is challenging to derive the backbone of the protein directly from such density maps, secondary structure elements such as helices and β-sheets can be computationally detected. Our work in this paper provides an approach to enumerate the top-ranked possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…However, the likely connections may be derived. Given the positions of a helices and b strands in a density map, one can match them with secondary structure sequence segments that can be predicted from the amino acid sequence to derive the overall topology of a protein chain (Al Nasr et al, 2011;Baker et al, 2011;Biswas et al, 2012;Lindert et al, 2012;Lu et al, 2008). Once the topology is determined, backbone and side chains can be constructed and evaluated using energy functions (Al Nasr et al, 2010;Lindert et al, 2012;Sun and He, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the likely connections may be derived. Given the positions of a helices and b strands in a density map, one can match them with secondary structure sequence segments that can be predicted from the amino acid sequence to derive the overall topology of a protein chain (Al Nasr et al, 2011;Baker et al, 2011;Biswas et al, 2012;Lindert et al, 2012;Lu et al, 2008). Once the topology is determined, backbone and side chains can be constructed and evaluated using energy functions (Al Nasr et al, 2010;Lindert et al, 2012;Sun and He, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The de novo modeling combines information from the density map and the amino acid sequence of the protein to derive the topology of secondary structure traces [21,23,[37][38][39]. A topology maps the secondary structure traces from the density map to the amino acid sequence, and therefore determines how the protein chain thread through the traces.…”
Section: Introductionmentioning
confidence: 99%
“…A topology maps the secondary structure traces from the density map to the amino acid sequence, and therefore determines how the protein chain thread through the traces. We previously showed that using a dynamic programming method combined with the K-shortest path algorithm, it takes Δ 2 time to rank the top K topologies using DP-TOSS [23,38]. Here N is the number of secondary structure traces detected in the density map and M is the number of secondary structure sequence segments, and Δ 1.…”
Section: Introductionmentioning
confidence: 99%
“…We previously formulated the SSE topology problem into a constraint graph problem and gave a dynamic programming algorithm for the simplest situation in which [27]. More importantly, our previous algorithm determines the optimal solution that often fails when the optimal solution is not the true topology due to the various errors in the data.…”
Section: Introductionmentioning
confidence: 99%